Does R&D, human capital and FDI matter for TFP in OECD countries?. Issue 4 (19th May 2019) - Tsamadias, Constantinos; Pegkas, Panagiotis; Mamatzakis, Emmanuel; Staikouras, Christos
ABSTRACT: This study investigates the interplay between research and development (R&D), human capital (HC), foreign direct investment (FDI) and total factor productivity (TFP) in OECD countries. We divide the sample into two sub-groups; the European and the non-European states so as to account for underlying country heterogeneity. The analysis follows a panel data approach over the period 1995–2015, taking into account the modelling on non-stationarity, long-run relationships and short-run dynamics with a panel VAR. Both R&D and HC have a positive effect on TFP, whilst FDI has a positive and significant effect only in the case of non-European countries. Moreover, the contribution of R&D is higher than that of HC and FDI in all cases. Thus, based on these findings, policymakers should design and implement policies to increase resources invested in R&D, with a consistent ongoing spending review, to attract foreign direct investment, especially for the majority of the European and some of the non-European countries and to improve education system on a more productive innovation and research base.